A novel antagonist of Toll-like receptors 7, 8 and 9 suppresses lupus disease-associated parameters in NZBW/F1 mice. (November 2013) - Zhu, Fu-Gang; Jiang, Weiwen; Bhagat, Lakshmi; Wang, Daqing; Yu, Dong; Tang, Jimmy X.; Kandimalla, Ekambar R.; La Monica, Nicola; Agrawal, Sudhir
Abstract Systemic Lupus Erythematosus is an autoimmune disease characterized by production of autoantibodies against nucleic acid-associated antigens. Endogenous DNA and RNA associated with these antigens stimulate inflammatory responses through Toll-like receptors (TLRs) and exacerbate lupus disease pathology. We have evaluated an antagonist of TLR7, 8 and 9 as a therapeutic agent in lupus-prone NZBW/F1 mice. NZBW/F1 mice treated with the antagonist had lower serum levels of autoantibodies targeting DNA, RNP, Smith antigen, SSA and SSB than did untreated mice. Reduction in blood urea nitrogen and proteinuria and improvements in kidney histopathology were observed in antagonist-treated mice. The antagonist treatment also reduced serum IL-12 and IL-1β and increased IL-10 levels. Levels of mRNA for IL-6, iNOS and IL-1β were lower in the kidneys and spleen of antagonist-treated mice than in those of untreated mice. Levels of mRNA for IP-10, TNFRSF9 and FASL were lower and IL-4 mRNA were higher in spleens of antagonist-treated mice than in spleens of untreated mice. mRNA for the inflammasome component NLRP3 was lower and mRNA for the antioxidant enzymes, catalase and glutathione peroxidase 1 was higher in the kidneys of antagonist-treated mice than in those of untreated mice. These results show that the antagonist of TLR7, 8 and 9 effectively inhibits inflammatory pathways involved in the development of lupus in NZBW/F1 mice and constitutes a potential therapeutic approach for the treatment of lupus and other autoimmune diseases.